ENVIRONMENTAL DIPLOMACY: HISTORY AND CURRENT ISSUES - Poda, Tetiana (Proceedings of the National Aviation University Series Philosophy Cultural, 2023)
The paper analyzes the history and the stages of the development of environmental diplomacy. Its achievements are summarized and the current state is described. Environmental diplomacy as a phenomenon of the XX-XXI centuries arose as a result of the world community's reaction to the threat of an ecological catastrophe. Environmental diplomacy is a complex and multifaceted phenomenon that develops at several levels: the global level, represented by the functioning of the UN and the activities of the EU; regional level of diplomacy: environmental activities conducted by the regional environmental institutes.